Static Output Feedback-Based DFIG Controller Design for the Wind-Driven Scheme - Bharti O.P.; Vardhan A.S.S.; Vardhan A.S.S.; Saket R.K.; Kothari D.P. (My University, 2025)
This paper presents DFIG-based WT schemes for WECS that are necessitated the appropriate control systems to get better performance with an efficient operation of the DFIG system. During the DFIG functioning both rotor and grid side converters play a very important role because these converters have controllers that control the DFIG-based WT system. The wind energy general idea and the DFIG working principle have been discussed properly. The sixth-order transfer function (T.F) DFIG model (considered a plant model) has been applied for controller design to the DFIG system in terms of Static Output Feedback Technique (SOF) and Genetic Algorithm (GA)-based optimization techniques. The SOF- and GA-based designed controllers have been implemented in the DFIG-based WT Simulink model for their performance analysis, in terms of output responses of three-phase terminal voltage, active power delivery and reactive power requirement to the grid along with DC-Link voltage. Also, these designed controllers are applied in the sixth-order DFIG system T.F model and get output responses concerning time and frequency domain specifications. At last, after the comparisons of output responses of both controllers in DFIG Simulink and T.F model cases it has been found that the SOF-based controller design scheme is better than GA-based technique for the DFIG-based WT system. Hence the SOF technique is the better alternative to designing a controller for (higher-order) DFIG-based WT systems. Abbreviations: Tr: Rise Time, Tp: Peak Time, Ts: Settling Time, Mp: Maximum Overshoot, Pc: Peak, GM: Gain Margin, PM: Phase Margin, Wgc: Gain crossover frequency, Wpc: Phase crossover frequency. © 2024 IETE.